2009
DOI: 10.1098/rsbl.2009.0670
|View full text |Cite
|
Sign up to set email alerts
|

Rowers' high: behavioural synchrony is correlated with elevated pain thresholds

Abstract: Physical exercise is known to stimulate the release of endorphins, creating a mild sense of euphoria that has rewarding properties. Using pain tolerance (a conventional non-invasive assay for endorphin release), we show that synchronized training in a college rowing crew creates a heightened endorphin surge compared with a similar training regime carried out alone. This heightened effect from synchronized activity may explain the sense of euphoria experienced during other social activities (such as laughter, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
236
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(242 citation statements)
references
References 21 publications
4
236
0
2
Order By: Relevance
“…Synchronous tapping, but not asynchronous tapping, generated higher affiliation ratings, but only when the synchrony was with another person, and not just experienced (i.e., tapping to a metronome) (Hove & Risen, 2009). Synchronized training in competitive rowers resulted in increased endorphin release (Cohen et al, 2010), suggesting a proximate mechanism motivating this kind of behavioral coordination. Behavioral entrainment is highly detectable, and can impact people's perceptions of the affiliation between the synchronizers.…”
Section: B Copying a Behavior Of Individual A But With Neither A Parmentioning
confidence: 99%
“…Synchronous tapping, but not asynchronous tapping, generated higher affiliation ratings, but only when the synchrony was with another person, and not just experienced (i.e., tapping to a metronome) (Hove & Risen, 2009). Synchronized training in competitive rowers resulted in increased endorphin release (Cohen et al, 2010), suggesting a proximate mechanism motivating this kind of behavioral coordination. Behavioral entrainment is highly detectable, and can impact people's perceptions of the affiliation between the synchronizers.…”
Section: B Copying a Behavior Of Individual A But With Neither A Parmentioning
confidence: 99%
“…In the experiment by Tunçgenç and colleagues (2015) with 12-month-old infants, it was found that synchronous movement in a nonmusical context influenced infant preferential reaching. In adults, increased pain thresholds were found following rowing synchronously with others versus alone (Cohen, Ejsmond-Frey, Knight, & Dunbar, 2010). Cooperation is encouraged by walking synchronously versus asynchronously (Wiltermuth & Heath, 2009).…”
Section: Oving In Time With Others Ormentioning
confidence: 99%
“…We also know that activities such as laughter, singing and dancing all lead to an enhanced sense of bonding towards those with whom one does these activities Pearce et al 2015;Tarr et al 2015Tarr et al , 2016Manninen et al, submitted), mainly because they trigger the endorphin system in the brain that underpins primate social bonding (Panksepp et al 1997;Curley and Keverne 2005;Dunbar 2010;Machin and Dunbar 2011). Since endorphins are involved in the control of feeding (Bakshi and Kelley 1993;Zhang and Kelley 2000;DiFeliceantonio et al 2012), the very fact of eating might itself trigger the endorphin system and promote bonding, and doing so socially may lead to the same kind of enhanced endorphin effects from behavioural synchrony that have been noted in physical exercise (Cohen et al 2010). Hence, people who eat often with others might be expected to have larger social networks and be happier and more satisfied with their lives, as well as being more engaged with their communities.…”
Section: Introductionmentioning
confidence: 99%